Manufacturing method of hydrophobic alginate beads, and air filter including the same
Patent Information
- Application Number
- KR1020250013104
- Authority / Receiving Office
- KR · KR
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2025-02-03
- Publication Date
- 2026-08-11
Smart Images

Figure PAT00001_ABST
Abstract
Description
Technology Field
[0001] The present invention relates to a method for manufacturing hydrophobic alginate beads for adsorbing fine dust and volatile organic compounds, and an air filter comprising the same. Background Technology
[0003] Particulate matter (PM) is generated by various causes, including industrial emissions, vehicle exhaust, and biomass combustion. Based on particle size (diameter), particulate matter is classified into PM10, PM2.5, and PM0.3. Ultrafine particulate matter, such as PM2.5 and PM0.3, enters the body through the respiratory system, causing serious health problems including respiratory and cardiovascular diseases. In addition, Volatile Organic Compounds (VOCs) are liquid or gaseous organic compounds with high vapor pressure that evaporate easily into the atmosphere. They act as a major cause of air quality deterioration by generating ozone and toxic byproducts through photochemical reactions in the atmosphere. Accordingly, there is a demand for the development of high-performance air filter materials capable of effectively removing particulate matter and volatile organic compounds.
[0004] Meanwhile, alginate, a natural polymer, is a polysaccharide that serves as a major component of the cell walls of brown algae and seaweed. Due to its excellent biocompatibility, biodegradability, and diverse physical properties, it is widely used as an additive in pharmaceuticals, cosmetics, and food. A representative application utilizing alginate is the alginate bead. Alginate beads exhibit superior performance in the adsorption and removal of various organic and inorganic contaminants and possess physically and chemically stable characteristics, making them widely utilized in academia and industry.
[0005] However, conventional alginate beads are generally manufactured in a size of several millimeters; this results in a low surface area, making effective adsorption of contaminants difficult, and the inability to easily control their size makes it difficult to ensure uniformity in filter performance. Furthermore, conventional alginates have hydrophilic properties, which limits their adsorption efficiency for hydrophobic contaminants such as volatile organic compounds (VOCs). Prior art literature
[0007] Korean Patent Publication No. 10-2020-0122773 (October 28, 2020) The problem to be solved
[0008] The present invention provides a method for manufacturing hydrophobic alginate beads having high adsorption performance for fine dust and volatile organic compounds emitted into the atmosphere through size control and surface treatment.
[0009] In addition, the present invention provides an air filter comprising hydrophobic alginate beads having high adsorption performance for fine dust and volatile organic compounds emitted into the atmosphere. means of solving the problem
[0011] A method for manufacturing hydrophobic alginate beads according to the present invention may include: S1) a step of manufacturing alginate beads by sequentially injecting an alginate solution containing oxidized carbon nanoparticles into an oil composition and a cation aqueous solution; and S2) a step of manufacturing hydrophobic alginate beads by coating the surface of the alginate beads with a hydrophobic material and heat-treating them.
[0012] The alginate solution containing the oxidized carbon nanoparticles according to one embodiment may contain 1 to 15 weight% of alginate and 0.01 to 0.5 weight% of oxidized carbon nanoparticles.
[0013] The oxidized carbon nanoparticles according to one embodiment may include one or more selected from the group consisting of oxidized charcoal, oxidized activated carbon, oxidized graphite, oxidized graphene, oxidized carbon nanotubes, oxidized fullerene, and oxidized amorphous carbon.
[0014] In step S1) according to one embodiment, the amount of alginate solution containing the oxidized carbon nanoparticles injected may be 0.1 to 10 mL.
[0015] In step S1) according to one embodiment, the injection time of the alginate solution containing the oxidized carbon nanoparticles may be 1 second to 10 minutes.
[0016] The oil composition according to one embodiment may include one or more selected from the group consisting of silicone oil, hexane oil, mineral oil, paraffin oil, isooctane, toluene, and dichloromethane.
[0017] The oil composition according to one embodiment may be a mixture of silicone oil and hexane oil in a volume ratio of 1:1 to 25.
[0018] The aqueous cation solution according to one embodiment may include one or more selected from the group consisting of calcium chloride (CaCl2), barium chloride (BaCl2), strontium chloride (SrCl2), magnesium chloride (MgCl2), aluminum chloride (AlCl3), and zinc chloride (ZnCl2).
[0019] According to one embodiment, the step S1) may further include a step of heat-treating the alginate beads to completely dry them.
[0020] According to one embodiment, the heat treatment can be performed at 10 to 100 ℃ for 1 to 24 hours.
[0021] The diameter of the alginate bead produced in step S1) according to one embodiment may be 1 to 20 mm.
[0022] The hydrophobic material according to one embodiment may include one or more selected from the group comprising polydimethylsiloxane (PDMS), diphenylpolydimethylsiloxane (DP), polymethylhydrosiloxane (PMHS), and hexamethyldisiloxane (HMDS).
[0023] In step S2) according to one embodiment, the coating may be performed at 20°C to 150°C for 1 minute to 5 hours.
[0024] In step S2) according to one embodiment, the heat treatment may be performed at 20 to 120 ℃ for 10 minutes to 24 hours.
[0025] According to one embodiment, the diameter of the hydrophobic alginate bead may be 2 mm to 10 mm.
[0026] In addition, the air filter according to the present invention may include alginate beads produced by the method for producing hydrophobic alginate beads.
[0027] The fine dust removal efficiency of the air filter according to one embodiment may be 90 to 99.9%.
[0028] The pressure drop of the air filter according to one embodiment may be 10 to 25 Pa. Effects of the invention
[0030] This invention utilizes a phase separation-induced synthesis method to maintain a large bead shape even upon complete drying, enabling its application as an air filter material and allowing for particle size control and the securing of mass production technology.
[0031] In addition, the present invention uniformly disperses nano-sized and micro-sized oxidized carbon nanoparticles inside alginate beads, thereby significantly improving the removal efficiency of fine dust (PM) and volatile organic compounds (VOCs).
[0032] In addition, the present invention can exhibit excellent adsorption performance against various pollutants by effectively controlling hydrophobicity and hydrophilicity through coating the surface of alginate beads with a hydrophobic material based on a siloxane-based polymer.
[0033] In addition, the present invention can solve the problem of causing environmental pollution during the waste disposal process when replacing filters by utilizing naturally biodegradable natural materials. Brief explanation of the drawing
[0035] FIG. 1 schematically illustrates a method for manufacturing alginate beads according to one embodiment of the present invention. Figure 2 shows carbon nanoparticles dispersed in water according to one embodiment of the present invention. Figure 3 shows a transmission electron microscope (TEM) image of oxidized carbon nanoparticles according to one embodiment of the present invention. Figure 4 shows alginate beads according to one embodiment of the present invention, arranged by size. Figure 5 shows the water contact angle of an alginate bead according to one embodiment of the present invention. FIG. 6 schematically illustrates an air filter including alginate beads according to one embodiment of the present invention. FIG. 7 shows an arrangement of alginate beads filled in an air filter according to one embodiment of the present invention. FIGS. 8 to 10 show the fine dust removal efficiency and pressure drop of an air filter including alginate beads according to one embodiment of the present invention. Specific details for implementing the invention
[0036] The embodiments described in this specification may be modified in various different forms, and the technology according to one embodiment is not limited to the embodiments described below. Furthermore, the embodiments of one embodiment are provided to more fully explain the present disclosure to those with average knowledge in the relevant technical field. Unless otherwise defined, technical and scientific terms used herein have the meanings commonly understood by those with ordinary knowledge in the technical field to which this invention pertains, and descriptions of known functions and configurations that could unnecessarily obscure the essence of the present invention are omitted in the following description and accompanying drawings.
[0037] Additionally, the singular form used in this specification and the appended claims may be intended to include the plural form unless specifically indicated otherwise in the context.
[0038] Furthermore, in this specification and the appended claims, terms such as "first," "second," etc. are used not in a limiting sense, but for the purpose of distinguishing one component from another.
[0039] Furthermore, in this specification and the appended claims, when a part such as a film (layer), region, or component is described as being located "on," "on top," "on the upper," "under," "on the lower," or "on the lower" of another part, this includes not only cases where a part is in contact with another part, but also cases where another part exists between the two parts.
[0040] Furthermore, terms such as "approximately" and "substantially" as used in this specification and the appended claims are used to mean at or near the stated value when inherent manufacturing and material tolerances are presented in the said meaning, and are used to prevent unscrupulous infringers from unfairly exploiting the disclosure in which precise or absolute values are mentioned to aid in understanding this specification and the appended claims.
[0041] Additionally, numeric ranges used in this specification include lower and upper limits and all values within the range, increments logically derived from the shape and width of the defined range, all of which are limited values, and all possible combinations of upper and lower limits of numeric ranges limited in different forms.
[0042] Furthermore, in this specification and the appended claims, terms such as "comprising" or "having" mean that the features or components described in the specification exist, and unless specifically limited, do not preclude the possibility that one or more other features or components may be added.
[0043] Additionally, in this specification, the term "bead" may mean alginate beads and / or hydrophobic alginate beads.
[0044] Hereinafter, the method for manufacturing hydrophobic alginate beads of the present invention and the air filter including the same will be described in detail with reference to the attached drawings.
[0046] A method for manufacturing hydrophobic alginate beads according to the present invention may include: S1) a step of manufacturing alginate beads by sequentially injecting an alginate solution containing oxidized carbon nanoparticles into an oil composition and a cation aqueous solution; and S2) a step of manufacturing hydrophobic alginate beads by coating the surface of the alginate beads with a hydrophobic material and heat-treating them.
[0047] Step S1) above is a step of manufacturing alginate beads using a phase-induced synthesis method. A phase-induced synthesis method is a method of synthesizing a material at the interface of two or more immiscible liquid phases.
[0048] As one embodiment, the alginate solution containing the oxidized carbon nanoparticles may comprise 1 to 15 weight% of alginate and 0.01 to 0.5 weight% of oxidized carbon nanoparticles. When the above range is satisfied, the oxidized carbon nanoparticles are uniformly dispersed inside the alginate beads, so the removal efficiency for fine dust and volatile organic compounds can be significantly improved.
[0049] In one embodiment, the alginate is not particularly limited as long as it is commonly used in the art. For example, it may include one or more selected from the group consisting of sodium alginate, calcium alginate, potassium alginate, and magnesium alginate. Preferably, it may be sodium alginate (SA), but is not limited thereto.
[0050] As one embodiment, the alginate solution containing the oxidized carbon nanoparticles may contain 1 wt%, 2 wt%, 3 wt%, 4 wt%, 5 wt%, 6 wt%, 7 wt%, 8 wt%, 9 wt%, 10 wt%, 11 wt%, 12 wt%, 13 wt%, 14 wt%, 15 wt% of alginate, or within a range between any two values listed herein. For example, it may be 1 to 15 wt%, 1 to 10 wt%, or 3 to 8 wt%, but is not limited thereto. When the above range is satisfied, uniform beads are formed, and the efficiency of removing fine dust and volatile organic compounds can be improved. In addition, if the alginate is less than 1 wt%, it is difficult to form uniform beads, making it unsuitable as an air filter material, and if the alginate exceeds 30 wt%, the inside of the beads becomes too dense, which may reduce the adsorption efficiency.
[0051] In one embodiment, the oxidized carbon nanoparticles are nano-sized particles in which oxygen functional groups (-OH, -COOH, -C=O, etc.) are introduced to the surface of carbon-based nanoparticles through a chemical or physical oxidation process. This oxidation treatment increases hydrophilicity, thereby improving adsorption performance and reactivity, which can enable various applications.
[0052] As an example, the oxidized carbon nanoparticles are not particularly limited as long as they are commonly used in the art. For example, they may include one or more selected from the group consisting of oxidized charcoal, oxidized activated carbon, oxidized graphite, oxidized graphene, oxidized carbon nanotubes, oxidized fullerene, and oxidized amorphous carbon. Preferably, they may be oxidized charcoal, but are not limited thereto.
[0053] In one embodiment, the alginate solution containing the oxidized carbon nanoparticles may contain 0.01 wt%, 0.02 wt%, 0.03 wt%, 0.04 wt%, 0.05 wt%, 0.06 wt%, 0.07 wt%, 0.08 wt%, 0.09 wt%, 0.1 wt%, 0.2 wt%, 0.3 wt%, 0.4 wt%, 0.5 wt% of the oxidized carbon nanoparticles, or within a range between any two of the values described herein. For example, it may be 0.01 to 0.5 wt%, 0.01 to 0.1 wt%, or 0.03 to 0.1 wt%, but is not limited thereto. When the above range is satisfied, the oxidized carbon nanoparticles can be uniformly dispersed inside the alginate beads. In addition, if the oxidized carbon nanoparticles are less than 0.01 weight%, the efficiency of removing fine dust and volatile organic compounds may decrease, and if the oxidized carbon nanoparticles exceed 10 weight%, the excessive nanoparticles may interfere with the formation of beads of alginate.
[0054] As one embodiment, the solvent of the alginate solution containing the oxidized carbon nanoparticles is not particularly limited as long as it is capable of dissolving the alginate and the oxidized carbon nanoparticles. For example, it may include one or more selected from the group consisting of distilled water, acetone, ethanol, and dimethyl sulfoxide (DMSO). Preferably, it may be distilled water (DIW), but is not limited thereto.
[0055] As one embodiment, the alginate solution containing the oxidized carbon nanoparticles may be ultrasonically treated to prevent aggregation of the oxidized carbon nanoparticles. The ultrasonically treated method is not particularly limited as long as it is a method commonly used in the art.
[0056] In one embodiment, the ultrasonic treatment time may be within a range of 1 minute, 2 minutes, 3 minutes, 4 minutes, 5 minutes, 6 minutes, 7 minutes, 8 minutes, 9 minutes, 10 minutes, 20 minutes, 30 minutes, 40 minutes, 50 minutes, 1 hour, 2 hours, 3 hours, 4 hours, 5 hours, 6 hours, 7 hours, or between any two values listed herein. For example, it may be from 1 minute to 7 hours, from 10 minutes to 3 hours, or from 1 hour to 2 hours, but is not limited thereto. When the above range is satisfied, the oxidized carbon nanoparticles can be uniformly dispersed without aggregation. In addition, if it falls outside the above range, the oxidized carbon nanoparticles may aggregate and not be uniformly distributed, or the alginate structure may be damaged, making it difficult to form uniform beads.
[0057] FIG. 1 schematically illustrates a method for manufacturing alginate beads according to one embodiment of the present invention. In one embodiment, an oil composition may be placed on top and a cationic aqueous solution on the bottom to form a phase separation interface. Accordingly, when an alginate solution containing the oxidized carbon nanoparticles is injected, the particles move from the oil composition to the cationic aqueous solution by gravity to produce alginate beads, but this is not limited thereto.
[0058] In one embodiment, when an alginate solution containing the oxidized carbon nanoparticles is injected into an oil composition in the form of droplets, the alginate solution maintains a droplet form within the oil because oil and water do not mix. Accordingly, the alginate solution droplets maintain stability, allowing for size control. In this process, the size of the alginate solution droplets is determined by the alginate concentration, the viscosity of the oil composition, the injection speed, etc., and is not particularly limited as long as the effects of the present invention are achieved.
[0059] As one embodiment, the injection amount of the alginate solution containing oxidized carbon nanoparticles in step S1) may be 0.1 mL, 0.2 mL, 0.3 mL, 0.4 mL, 0.5 mL, 0.6 mL, 0.7 mL, 0.8 mL, 0.9 mL, 1 mL, 2 mL, 3 mL, 4 mL, 5 mL, 6 mL, 7 mL, 8 mL, 9 mL, 10 mL, or within a range between any two of the values listed herein. For example, it may be 0.1 to 10 mL, 0.1 to 5 mL, or 1 to 5 mL, but is not limited thereto. When the above range is satisfied, the alginate solution droplet is stably maintained in the oil composition, making it easy to control the bead size. In addition, if it falls outside the above range, the alginate solution droplet moves irregularly within the oil composition, making it difficult to form uniform beads.
[0060] In one embodiment, the injection time of the alginate solution containing oxidized carbon nanoparticles in step S1) may be 1 second, 2 seconds, 3 seconds, 4 seconds, 5 seconds, 6 seconds, 7 seconds, 8 seconds, 9 seconds, 10 seconds, 20 seconds, 30 seconds, 40 seconds, 50 seconds, 1 minute, 2 minutes, 3 minutes, 4 minutes, 5 minutes, 6 minutes, 7 minutes, 8 minutes, 9 minutes, 10 minutes, or within a range between any two of the values listed herein. For example, it may be from 1 second to 10 minutes, from 3 seconds to 3 minutes, or from 10 seconds to 1 minute, but is not limited thereto. If the above range is satisfied, it may be easy to control the shape and size of the alginate solution droplets. In addition, if it falls outside the above range, the size and uniformity of the alginate solution droplets may be unstable, making it difficult to form uniform beads.
[0061] In one embodiment, the oil composition is not particularly limited as long as it is a non-polar oil that does not mix with the alginate solution containing the oxidized carbon nanoparticles. For example, it may include one or more selected from the group consisting of silicone oil, hexane oil, mineral oil, paraffin oil, isooctane, toluene, and dichloromethane. Preferably, it may be a mixed solution of silicone oil and hexane oil, but is not limited thereto.
[0062] In one embodiment, the volume ratio of the silicone oil and the hexane oil may be 1:1, 1:2, 1:3, 1:4, 1:5, 1:6, 1:7, 1:8, 1:9, 1:10, 1:11, 1:12, 1:13, 1:14, 1:15, 1:16, 1:17, 1:18, 1:19, 1:20, 1:21, 1:22, 1:23, 1:24, 1:25, or within a range between any two of the values listed herein. For example, it may be 1:1 to 25, 1:10 to 25, or 1:15 to 20, but is not limited thereto. When the above range is satisfied, the phase separation-induced synthesis proceeds smoothly, making it easy to control the bead size. In addition, if the bead size is outside the above range, it is difficult to control, and it may not be formed uniformly.
[0063] In one embodiment, the shape and size of the alginate solution containing the oxidized carbon nanoparticles are determined in the oil composition, and when it moves to the cation aqueous solution by gravity, the crosslinking of the alginate occurs immediately through an ion exchange reaction, and the shape and size can be fixed in the form of beads.
[0064] As an example, the aqueous cation solution is not particularly limited as long as it is one commonly used in the art. For example, it may include one or more selected from the group consisting of calcium chloride (CaCl2), barium chloride (BaCl2), strontium chloride (SrCl2), magnesium chloride (MgCl2), aluminum chloride (AlCl3), and zinc chloride (ZnCl2). Preferably, it may be calcium chloride, but is not limited thereto.
[0065] In one embodiment, the cation concentration of the aqueous cation solution may be within a range of 1 wt%, 2 wt%, 3 wt%, 4 wt%, 5 wt%, 6 wt%, 7 wt%, 8 wt%, 9 wt%, 10 wt%, 11 wt%, 12 wt%, 13 wt%, 14 wt%, 15 wt%, 16 wt%, 17 wt%, 18 wt%, 19 wt%, 20 wt%, or between any two of the values listed herein. For example, it may be 1 to 20 wt%, 1 to 15 wt%, or 1 to 10 wt%, but is not limited thereto. When the above range is satisfied, the cross-linking reaction of the alginate proceeds to form stable beads. In addition, if it falls outside the above range, the cross-linking reaction may be insufficient or excessive, making it difficult to form uniform beads.
[0066] In one example, stirring may be performed for 24 hours to ensure sufficient ion exchange during the crosslinking process by the ion exchange reaction between alginate and cations, but is not limited thereto.
[0067] In one embodiment, step S1) may further include the step of heat-treating the alginate beads to completely dry them. The heat treatment temperature may be within a range between any two values among 10 ℃, 20 ℃, 30 ℃, 40 ℃, 50 ℃, 60 ℃, 70 ℃, 80 ℃, 90 ℃, 100 ℃, or any two values listed herein. For example, it may be 10 to 100 ℃, 20 to 70 ℃, or 30 to 50 ℃, but is not limited thereto. In addition, the heat treatment time may be within a range between any two values listed herein, or 1 hour, 2 hours, 3 hours, 4 hours, 5 hours, 6 hours, 7 hours, 8 hours, 9 hours, 10 hours, 11 hours, 12 hours, 13 hours, 14 hours, 15 hours, 16 hours, 17 hours, 18 hours, 19 hours, 20 hours, 21 hours, 22 hours, 23 hours, 24 hours. For example, it may be 1 to 24 hours, 5 to 24 hours, or 10 to 24 hours, but is not limited thereto. If the above range is satisfied, shrinkage of the bead can be minimized even after drying, and if it falls outside the above range, cracks may occur in the bead as it shrinks.
[0068] As one embodiment, the diameter of the alginate beads prepared in step S1) may be 2 mm, 3 mm, 4 mm, 5 mm, 6 mm, 7 mm, 8 mm, 9 mm, 10 mm, 11 mm, 12 mm, 13 mm, 14 mm, 15 mm, 16 mm, 17 mm, 18 mm, 19 mm, 20 mm, or within a range between any two of the values listed herein. For example, it may be 1 to 20 mm, 2 to 15 mm, or 5 to 10 mm, but is not limited thereto. When satisfying the above range, it can have high adsorption performance for fine dust and volatile organic compounds emitted into the atmosphere while minimizing pressure loss when used as an air filter material.
[0069] Step S2) above is a step of manufacturing hydrophobic alginate beads by coating the surface of the alginate beads with a hydrophobic material and heat-treating them. Since alginate is a hydrophilic material, it has a high affinity for water, which limits its adsorption efficiency for hydrophobic pollutants such as volatile organic compounds (VOCs). Accordingly, the adsorption performance of fine dust and volatile organic compounds can be optimized by controlling surface characteristics through a hydrophobic coating on the surface of the alginate.
[0070] As an example, the hydrophobic material is not particularly limited as long as it is commonly used in the art. For example, as a siloxane-based polymer, it may include one or more selected from the group comprising polydimethylsiloxane (PDMS), diphenylpolydimethylsiloxane (DP), polymethylhydrosiloxane (PMHS), and hexamethyldisiloxane (HMDS). Preferably, it may be polydimethylsiloxane (PDMS), but is not limited thereto.
[0071] In one embodiment, the coating temperature in step S2) may be within a range of 20 ℃, 30 ℃, 40 ℃, 50 ℃, 60 ℃, 70 ℃, 80 ℃, 90 ℃, 100 ℃, 110 ℃, 120 ℃, 130 ℃, 140 ℃, 150 ℃, or between any two of the values listed herein. For example, it may be 20 to 150 ℃, 50 to 120 ℃, or 80 to 120 ℃, but is not limited thereto. In addition, the coating time may be within a range of 1 minute, 2 minutes, 3 minutes, 4 minutes, 5 minutes, 6 minutes, 7 minutes, 8 minutes, 9 minutes, 10 minutes, 20 minutes, 30 minutes, 40 minutes, 50 minutes, 1 hour, 2 hours, 3 hours, 4 hours, 5 hours, or between any two values listed herein. For example, it may be from 1 minute to 5 hours, from 10 minutes to 3 hours, or from 30 minutes to 1 hour, but is not limited thereto. A hydrophobic material can be uniformly coated on the surface of an alginate bead satisfying the above range. In addition, if it falls outside the above range, the hydrophobic material may be unevenly coated on the surface of the alginate bead, and the hydrophobicity may be reduced.
[0072] In one embodiment, the heat treatment temperature may be within a range between any two values among 20 ℃, 30 ℃, 40 ℃, 50 ℃, 60 ℃, 70 ℃, 80 ℃, 90 ℃, 100 ℃, 110 ℃, 120 ℃, or any two values listed herein. For example, it may be 20 to 120 ℃, 50 to 120 ℃, or 100 to 120 ℃, but is not limited thereto. In addition, the heat treatment time may be within a range of 10 minutes, 20 minutes, 30 minutes, 40 minutes, 50 minutes, 1 hour, 2 hours, 3 hours, 4 hours, 5 hours, 6 hours, 7 hours, 8 hours, 9 hours, 10 hours, 11 hours, 12 hours, 13 hours, 14 hours, 15 hours, 16 hours, 17 hours, 18 hours, 19 hours, 20 hours, 21 hours, 22 hours, 23 hours, 24 hours, or between any two of the values listed herein. For example, it may be from 10 minutes to 24 hours, from 30 minutes to 24 hours, or from 1 to 2 hours, but is not limited thereto. A hydrophobic material can be uniformly cured on the surface of an alginate bead satisfying the above range. In addition, if it falls outside the above range, the hydrophobic material may be partially cured or damage may occur on the surface of the alginate bead.
[0073] In one embodiment, the hydrophobic coating layer formed by coating the hydrophobic material on the surface of the alginate beads may have a water contact angle of 90°. The size of the hydrophobic alginate beads prepared in step S2) may have a water contact angle of 90°, 100°, 110°, 120°, 130°, 140°, 150°, or within a range between any two of the values listed herein. For example, it may be 90 to 150°, 90 to 140°, or 100 to 140°, but is not limited thereto.
[0074] As one embodiment, the diameter of the hydrophobic alginate beads prepared in step S2) may be 2 mm, 3 mm, 4 mm, 5 mm, 6 mm, 7 mm, 8 mm, 9 mm, 10 mm, 11 mm, 12 mm, 13 mm, 14 mm, 15 mm, 16 mm, 17 mm, 18 mm, 19 mm, 20 mm, or within a range between any two of the values listed herein. For example, it may be 1 to 20 mm, 2 to 15 mm, or 5 to 10 mm, but is not limited thereto. When satisfying the above range, it can have high adsorption performance for fine dust and volatile organic compounds emitted into the atmosphere while minimizing pressure loss when used as an air filter material.
[0075] The hydrophobic alginate beads according to the present invention have significantly improved removal efficiency for fine dust (PM) and volatile organic compounds (VOCs) by uniformly dispersing nano-sized and micro-sized oxidized carbon nanoparticles within them. In addition, by coating with a hydrophobic material based on a siloxane-based polymer, hydrophobicity and hydrophilicity can be effectively controlled, thereby enabling excellent adsorption performance for various pollutants.
[0076] In addition, the present invention may provide an air filter comprising hydrophobic alginate beads manufactured according to a method for manufacturing hydrophobic alginate beads. A specific description of the hydrophobic alginate beads may include all the details described above in the method for manufacturing hydrophobic alginate beads.
[0077] In one embodiment, the air filter can have high adsorption performance for fine dust emitted into the atmosphere while minimizing pressure loss.
[0078] In one embodiment, the fine dust removal efficiency of the air filter may be 90%, 90.5%, 91%, 91.5%, 92%, 92.5%, 93%, 93.5%, 94%, 94.5%, 95%, 95.5%, 96%, 96.5%, 97%, 97.5%, 98%, 98.5%, 99%, 99.5%, 99.9%, or within a range between any two of the values listed herein. For example, it may be 90% to 99.9%, 90% to 99.5%, or 95% to 99.5%, but is not limited thereto.
[0079] In one embodiment, the pressure drop of the air filter may be within a range between any two values among 10 Pa, 11 Pa, 12 Pa, 13 Pa, 14 Pa, 15 Pa, 16 Pa, 17 Pa, 18 Pa, 19 Pa, 20 Pa, 21 Pa, 22 Pa, 23 Pa, 24 Pa, 25 Pa, or values listed herein. For example, it may be 10 to 25 Pa, 10 to 20 Pa, or 15 to 20 Pa, but is not limited thereto.
[0080] Therefore, the present invention utilizes a phase separation-induced synthesis method to maintain a large bead shape even upon complete drying, demonstrating not only excellent removal efficiency but also low pressure drop performance, making it applicable as an air filter material.
[0082] Examples and experimental examples are described below with specific examples. However, the examples and experimental examples described below are merely illustrative of some aspects, and the technology described in this specification is not limited thereto.
[0084] <Example 1>
[0085] Carbon nanoparticles were obtained on the surface of a plate by contacting a silicon plate with the candle flame during the incomplete combustion of the candle. The carbon nanoparticles were placed in a mixed solution of 30 mL of sulfuric acid and 10 mL of nitric acid and sonicated for 12 hours, after which distilled water was added and the mixture was centrifuged three times to obtain oxidized carbon nanoparticles. An oxidized carbon nanoparticle solution was prepared by adding 1 mL of distilled water per 1 mg of the oxidized carbon nanoparticles.
[0087] <Example 2>
[0088] An alginate solution containing oxidized carbon nanoparticles was prepared by mixing 290 mL of a 6 wt% alginate solution with 10 mL of a 50 wt% oxidized carbon nanoparticle solution prepared in Example 1.
[0089] An oil composition in which silicone oil and hexane oil were mixed in a volume ratio of 1:19 was placed at the top of a container, and a 2 wt% aqueous solution of CaCl2 cations was placed at the bottom to create a phase separation interface.
[0090] 0.35 mL of an alginate solution containing the above-mentioned oxidized carbon nanoparticles was injected into the oil composition, and beads that fell into the cation aqueous solution by gravity were crosslinked at room temperature for 1 hour, and then alginate beads were prepared by stirring at room temperature for 24 hours in an 8 wt% CaCl2 solution. Subsequently, the alginate beads were dried at room temperature (25 ℃) for 12 hours, and then completely dried by heat treatment in an oven at 40 ℃ for 20 hours.
[0091] The above completely dried alginate beads were immersed in a polydimethylsiloxane (PDMS) solution for 1 hour, and then heated at 100°C for 1 hour to produce alginate beads with a diameter of 2 mm.
[0093] <Example 3>
[0094] Hydrophobic alginate beads with a diameter of 3 mm were prepared by carrying out the same procedure as in Example 2 above, except that 0.5 mL of an alginate solution containing oxidized carbon nanoparticles was injected.
[0096] <Example 4>
[0097] Hydrophobic alginate beads with a diameter of 4 mm were prepared by carrying out the same procedure as in Example 2 above, except that 1 mL of an alginate solution containing oxidized carbon nanoparticles was injected.
[0099] <Example 5>
[0100] Hydrophobic alginate beads with a diameter of 5 mm were prepared by carrying out the same procedure as in Example 2 above, except that 1.95 mL of an alginate solution containing oxidized carbon nanoparticles was injected.
[0102] <Example 6>
[0103] Hydrophobic alginate beads with a diameter of 7 mm were prepared by carrying out the same procedure as in Example 2 above, except that 2.8 mL of an alginate solution containing oxidized carbon nanoparticles was injected.
[0105] <Example 7>
[0106] Hydrophobic alginate beads with a diameter of 9 mm were prepared by carrying out the same procedure as in Example 2 above, except that 3.5 mL of an alginate solution containing oxidized carbon nanoparticles was injected.
[0108] <Example 8>
[0109] An air filter was manufactured by filling the interior, composed of stainless steel mesh and hardboard in a volume ratio of 4:16, with hydrophobic alginate beads prepared in Example 4 and alginate beads of Comparative Example 2.
[0111] <Example 9>
[0112] An air filter was manufactured by filling the interior, which consisted of stainless steel mesh and hardboard in a volume ratio of 4:16, with the hydrophobic alginate beads prepared in Examples 3 and 4 and the alginate beads of Comparative Example 2.
[0114] <Comparative Example 1>
[0115] Carbon nanoparticles that were not oxidized in Example 1 above
[0117] <Comparative Example 2>
[0118] Conventional 1 mm alginate beads
[0120] <Comparative Example 3>
[0121] An air filter was manufactured by filling the alginate beads of Comparative Example 2 with a stainless steel mesh and a hardboard composed of a volume ratio of 4:16.
[0123] <Experimental Example 1> Analysis of Oxidized Carbon Nanoparticles
[0124] The oxidized carbon nanoparticles prepared in Example 1 were analyzed.
[0125] Figure 2 shows carbon nanoparticles dispersed in water according to an embodiment of the present invention. Images of carbon nanoparticles dispersed in water were compared to confirm the state of the carbon nanoparticles following oxidation treatment. (a) is the carbon nanoparticle (CS) of Comparative Example 1, and (b) is the oxidized carbon nanoparticle (O-CS) of Example 1. The carbon nanoparticle of Comparative Example 1 exhibited hydrophobic characteristics and appeared to float or aggregate on the water surface. In contrast, the oxidized carbon nanoparticle of Example 1 showed improved hydrophilicity and appeared to be stably dispersed in water. In particular, the oxidized carbon nanoparticle of Example 1 maintained its dispersed state even after several months, indicating that the functional groups on the surface changed due to oxidation, thereby improving hydrophilicity.
[0126] Figure 3 shows a transmission electron microscope (TEM) image of oxidized carbon nanoparticles according to one embodiment of the present invention. The oxidized carbon nanoparticles of Example 1 have a spherical structure, and the average particle size was measured to be approximately 42 nm. In addition, the size distribution is relatively uniform, which indicates the uniformity of the manufacturing process.
[0127] Accordingly, it was confirmed that the hydrophilicity of carbon nanoparticles was effectively modified through oxidation treatment, and that oxidized carbon nanoparticles with excellent stability and uniformity in both physical and chemical properties could be produced.
[0129] <Experimental Example 2> Comparison of Alginate Bead Sizes
[0130] The sizes of the alginate beads prepared in Examples 2 to 7 were compared.
[0131] FIG. 4 shows alginate beads according to one embodiment of the present invention by size. a) is an alginate bead before complete drying, and b) to g) are alginate beads after complete drying.
[0133] Example 2 Example 3 Example 4 Example 5 Example 6 Example 7 Infusion amount 0.35 mL 0.5 mL 1 mL 1.95 mL 2.8 mL 3.5 mL Diameter before complete drying 5 mm 6.7 mm 8 mm 10 mm 12 mm 15 mm Diameter after complete drying 2 mm 3 mm 4 mm 5 mm 7 mm 9 mm
[0135] Table 1 shows the sizes of alginate beads prepared in Examples 2 to 7 of the present invention. Conventional alginate beads were prepared with a diameter of 1 to 2 mm or less after complete drying, whereas the alginate beads according to the present invention were prepared with a diameter of 2 mm or more after complete drying. Accordingly, the alginate beads according to the present invention maintain a large bead shape even during drying, making them suitable for application as air filter materials.
[0137] <Experimental Example 3> Evaluation of Hydrophobicity of Alginate Beads
[0138] To evaluate the hydrophobic properties of alginate beads, the water contact angle (θ) was measured. Using a contact angle measuring instrument (SEO, Phoenix 300Touch), the water contact angle formed by dropping water droplets onto the surface of the alginate beads was repeatedly measured from 1 second to 15 seconds.
[0139] Figure 5 shows the water contact angle of an alginate bead according to one embodiment of the present invention. In the conventional alginate bead of Comparative Example 2, water droplets on the surface were gradually absorbed between 1 second and 15 seconds, and the water contact angle was measured to be 0°. Accordingly, it was confirmed that the alginate bead of Comparative Example 2 is hydrophilic. On the other hand, in the hydrophobic alginate bead of Example 2, water droplets were not absorbed on the surface but remained attached, and the water contact angle was measured to be 121°, confirming that the surface was completely modified to be hydrophobic.
[0140] Accordingly, the hydrophobic alginate beads prepared in Example 2 can have their hydrophobic and hydrophilic properties controlled by coating their surface with a siloxane-based polymer-based hydrophobic material, thereby exhibiting excellent adsorption performance against various pollutants.
[0142] <Experimental Example 4> Evaluation of Fine Dust Removal Performance
[0143] The fine dust removal performance of air filters containing alginate beads was compared.
[0144] FIG. 6 schematically illustrates an air filter containing alginate beads according to an embodiment of the present invention. Fine dust was formed by burning an incense stick in a 500 mL round-bottom flask connected to the left side of the air filter, and then air containing fine dust was introduced into the air filter connected to the round-bottom flask. A fine dust concentration meter was installed on the right side of the air filter to measure the efficiency of removing fine dust from the air passing through the air filter and being discharged to the right.
[0145] FIG. 7 shows the arrangement of alginate beads filled in an air filter according to an embodiment of the present invention. The air filter forms a filter layer by mixing the beads in a constant ratio according to their size. The filter layer consists of beads with diameters of 1 mm, 3 mm, 4 mm, and 5 mm. 1 mm beads are represented as yellow spheres, and 3 mm or 5 mm beads are represented as white spheres. Additionally, 4 mm beads are arranged in black, blue, and red colors for each layer within the air filter. The bead combination is determined experimentally to optimize removal efficiency and pressure drop, and all removal efficiency and pressure drop experiments were measured at a flow rate of 1 m / s.
[0146] FIGS. 8 to 10 illustrate the fine dust removal efficiency and pressure drop of an air filter containing alginate beads according to an embodiment of the present invention. Pressure drop is the pressure difference between the front and back surfaces of the filter when air passes through the filter. The greater the pressure drop, the worse the performance of the filter.
[0147] Figure 8 is a graph showing the fine dust removal efficiency and pressure drop of the air filter manufactured in Comparative Example 3. At a flow rate of 1 m / s, it showed removal efficiencies of 88.4% and 98.5% for PM2.5 and PM10 fine dust, respectively, and a pressure drop of 23 Pa.
[0148] Figure 9 is a graph showing the fine dust removal efficiency and pressure drop of the air filter manufactured in Example 8. The fine dust removal efficiency and pressure drop were measured for each number (15, 14, 13, 12, 11) by adding hydrophobic alginate beads with a diameter of 4 mm to alginate beads with a diameter of 1 mm. From 15 to 11, the removal efficiencies for PM2.5 fine dust were 95.0, 94.2, 93.0, 92.0, and 91.4%, the removal efficiencies for PM10 fine dust were 99.1, 99.0, 98.8, 98.8, and 98.0%, and the pressure drops were 17, 18, 18, 20, and 21 Pa, respectively. This is because as the number of 4 mm beads in the air filter decreases, the porosity decreases and the amount of fine dust that can be adsorbed decreases, and as 1 mm beads with small porosity are filled instead, the pressure drop increases.
[0149] Figure 10 is a graph showing the fine dust removal efficiency and pressure drop of the air filter manufactured in Example 9. At a flow rate of 1 m / s, it showed a removal efficiency of 88.4% and a pressure drop of 23 Pa for fine dust with a diameter of 2.5 μm. Fine dust removal efficiency and pressure drop were measured by adding 3 mm diameter hydrophobic alginate beads to 1 mm diameter alginate beads and 15 4 mm diameter hydrophobic alginate beads, according to the number of beads (8, 6, 4, 2). From 8 to 2 beads, removal efficiencies of 95.3%, 94.9%, 94.2%, and 94.1% were observed for PM2.5 fine dust, removal efficiencies of 99.4%, 99.1%, 98.5%, and 98.7% were observed for PM10 fine dust, and pressure drops of 16, 17, 17, and 18 Pa were observed. This is because the fine dust removal efficiency and pressure drop decreased as the proportion of hydrophobic alginate in the air filter increased. Therefore, it can be seen that the hydrophobic coating on the surface of the hydrophobic alginate lowers the energy of the air filter surface, preventing the detachment of fine dust and contributing to the reduction in removal efficiency and pressure drop.
[0151] As described above, the present invention has been explained in this specification by specific details and limited embodiments, but this is provided only to aid in a more comprehensive understanding of the invention, and the invention is not limited to the above embodiments. A person skilled in the art to which the invention pertains can make various modifications and variations from this description. Accordingly, the concept described in this specification should not be limited to the described embodiments, and all things equivalent to or having equivalent variations to the claims set forth below, as well as the claims themselves, shall be considered to fall within the scope of the concept described in this specification.
Claims
Claim 1 S1) a step of producing alginate beads by sequentially injecting an alginate solution containing oxidized carbon nanoparticles into an oil composition and a cation aqueous solution; and S2) a step of producing hydrophobic alginate beads by coating the surface of the alginate beads with a hydrophobic material and heat-treating them; a method for producing hydrophobic alginate beads. Claim 2 A method for manufacturing hydrophobic alginate beads according to claim 1, wherein the alginate solution containing the oxidized carbon nanoparticles comprises 1 to 15 weight% of alginate and 0.01 to 0.5 weight% of oxidized carbon nanoparticles. Claim 3 A method for manufacturing hydrophobic alginate beads according to claim 1, wherein the oxidized carbon nanoparticle comprises one or more selected from the group consisting of oxidized charcoal, oxidized activated carbon, oxidized graphite, oxidized graphene, oxidized carbon nanotubes, oxidized fullerene, and oxidized amorphous carbon. Claim 4 A method for manufacturing hydrophobic alginate beads according to claim 1, wherein the injection amount of the alginate solution containing the oxidized carbon nanoparticles in step S1) is 0.1 to 10 mL. Claim 5 A method for manufacturing hydrophobic alginate beads according to claim 1, wherein the injection time of the alginate solution containing the oxidized carbon nanoparticles in step S1) is 1 second to 10 minutes. Claim 6 A method for manufacturing hydrophobic alginate beads according to claim 1, wherein the oil composition comprises one or more selected from the group consisting of silicone oil, hexane oil, mineral oil, paraffin oil, isooctane, toluene, and dichloromethane. Claim 7 A method for manufacturing hydrophobic alginate beads according to claim 6, wherein the oil composition is a mixture of silicone oil and hexane oil in a volume ratio of 1:1 to 25. Claim 8 A method for manufacturing hydrophobic alginate beads according to claim 1, wherein the aqueous cation solution comprises one or more selected from the group consisting of calcium chloride (CaCl2), barium chloride (BaCl2), strontium chloride (SrCl2), magnesium chloride (MgCl2), aluminum chloride (AlCl3), and zinc chloride (ZnCl2). Claim 9 A method for manufacturing hydrophobic alginate beads, wherein, in claim 1, step S1) further comprises the step of heat-treating the alginate beads to completely dry them. Claim 10 A method for manufacturing hydrophobic alginate beads according to claim 9, wherein the heat treatment is performed at 10 to 100 ℃ for 1 to 24 hours. Claim 11 A method for manufacturing hydrophobic alginate beads according to claim 1, wherein the diameter of the alginate beads manufactured in step S1) is 1 to 20 mm. Claim 12 A method for manufacturing hydrophobic alginate beads according to claim 1, wherein the hydrophobic material comprises one or more selected from the group comprising polydimethylsiloxane (PDMS), diphenylpolydimethylsiloxane (DP), polymethylhydrosiloxane (PMHS), and hexamethyldisiloxane (HMDS). Claim 13 A method for manufacturing hydrophobic alginate beads according to claim 1, wherein in step S2), the coating is performed at 20 ℃ to 150 ℃ for 1 minute to 5 hours. Claim 14 A method for manufacturing hydrophobic alginate beads according to claim 1, wherein in step S2), the heat treatment is performed at 20 to 120 ℃ for 10 minutes to 24 hours. Claim 15 A method for manufacturing alginate beads according to claim 1, wherein the diameter of the hydrophobic alginate beads is 2 mm to 10 mm. Claim 16 An air filter comprising alginate beads manufactured by the method of any one of claims 1 to 15. Claim 17 In claim 16, an air filter having a fine dust removal efficiency of 90 to 99.9%. Claim 18 In claim 16, an air filter having a pressure drop of 10 to 25 Pa.